2019
DOI: 10.1002/app.47979
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactions affecting halloysite dispersion in epoxy nanocomposites

Abstract: Halloysite nanotubes (HNTs) have attracted a technologic and scientific attention as reinforcements of epoxy-based nanocomposites. However, their reported interaction with epoxy matrices is varied and the controlled dispersion of HNTs is still a challenge. In this work, we study the effect of chemical reactions taking place in the dispersion process of halloysite and their possible influence in the composite's properties. HNTs' surface was modified through an alkaline treatment and by grafting two aminosilanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…A detailed description of the chemical characterization of the nanoclays can be found in a previous work. 44 The fluorinated modifier used to functionalize the surface of HNT was 1H,1H,2H,2H perfluorooctyltriethoxysilane (PFOTES, Worldyachem Co., China). Other reactants and solvents employed in surface and bulk modifications were TEOS (Merk, Buenos Aires), ammonia 28 wt.% and anhydrous ethanol (Biopack, Buenos Aires).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed description of the chemical characterization of the nanoclays can be found in a previous work. 44 The fluorinated modifier used to functionalize the surface of HNT was 1H,1H,2H,2H perfluorooctyltriethoxysilane (PFOTES, Worldyachem Co., China). Other reactants and solvents employed in surface and bulk modifications were TEOS (Merk, Buenos Aires), ammonia 28 wt.% and anhydrous ethanol (Biopack, Buenos Aires).…”
Section: Methodsmentioning
confidence: 99%
“…Such a wide range of degradation temperature is almost well-known for the silane chains degradation. 44…”
Section: Thermal Degradation Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Тщательный обзор литературы показал, что улучшен ная межповерхностная адгезия между галлуазитом и эпоксидной смо лой -многообещающий способ достижения эффективного улучшения механических свойств всех композиций. Модификация поверхности и прививка ГНТ аминосиланами, а также гибридные нанонаполнители (ГНТ и УНТ) предложены для создания эффективной передачи нагрузки между матрицей и арматурой [42,54]. Дальнейшие исследования в этой области могут улучшить армирующую способность эпоксидной матрицы при малом содержании ГНТ.…”
Section: заключениеunclassified
“…The shell composed of polyphosphazene (PZM) effectively promotes the interfacial interaction between HNTs and epoxy resin matrix. S anchez M et al 27 modified the surface of HNTs by alkali treatment and grafting of two different structures of amino silanes. The results showed that a chemical bond network could be formed between epoxy resin and HNTs.…”
Section: Introductionmentioning
confidence: 99%